Reassessing the Discourses on Legal Ethics in the Age of AI in Indonesia: Prospects and Obstacles - Idaman; Yuli Prasanti; Yuli Wailussy; Waode Nurul Putri Anastasia; Waode Putri Cahya Mulianingsih; Sitti Magfirah Salsabila; Sitti Hikmah Ayu Rusada; Salsa Dwi Faradiva (Journal of Law, Social Science and Management, 2025)
Background: Artificial intelligence has changed the way of looking and practicing law in a number of countries, including Indonesia. The legal profession experiences a number of challenges, as well as opportunities in this AI era. If so far, the work of the legal profession has relied on humans, in the era of AI, these jobs have turned into mechanical or robotic work. Although AI facilitates the performance of law enforcement apparatus, it turns out that there is a legal-ethical problem, in the form of ensuring that the performance of law enforcement apparatus is more transparent, accountable, and non-plagiarism in making law decisions. Objective: This research aims to analyze the opportunities and challenges of the legal profession in the era of artificial intelligence. Method: The method used in this study is a literature method, researching and documenting a number of literature and relationships related to the legal profession in the AI era. Results: The legal profession, which often involves human performance and moral judgments, still cannot be completely replaced by computer algorithms. The use of artificial intelligence is only to help the work of the legal profession. In many ways, human work is still required to complement the data accuracy of the data prepared by AI. Conclusion: the digital era offers great opportunities for the legal profession. Technology can be used to improve efficiency, expand access to justice, and provide more inclusive and transparent legal services. Legal professionals who are able to adapt and use technology wisely will be more relevant and needed in the future.,